The endogeneity approach of the theory of optimum currency areas: what does it mean for ASEAN + 3? - Horst Löchel; Stefan Baumann (HfB - Business School of Finance & Management, 2006)
The paper analyzes if and how the experiences of European integration can be used for the progress of East Asia integration especially of the ASEAN+3 countries1. Of special interest is the relevance of the new endogeneity approach of monetary integration for East Asia. The question is discussed in theoretical as well as in empirical terms. It can be shown that despite of the extensive gap between the level and the process of regional integration in Europe and East Asia there exist some conclusions of the endogeneity approach which can be useful for integration in East Asia as well. In practical terms it is concluded that monetary integration in East Asia could make progress via sub grouping of clusters of countries at best with the instrument of a kind of an 'Asian snake' similar to the European exchange rate system in the early 70's.
urn:nbn:de:101:1-2008082728
Keywords: E42; F15; F33; F42; O19; 330; Regional Integration; Optimum Currency Area; EMU; ASEAN + 3